COOPERATIVE LEARNING : ALTERNATIF UNTUK MENINGKATKAN COMMUNICATION SKILL PADA SEKOLAH BOARDING - Rismawati, Noviana; Nafiati, Dewi Amaliah; Azami, Tomi; Hendaryati, Neni (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
The teacher's role in improving students' communication skills when learning economics in boarding-based schools has a big influence in the classroom. Teachers must know the appropriate steps to determine the success of learning through the cooperative learning model. The cooperative learning model can improve critical thinking skills, formulate arguments, and work together to solve problems. The aim of this research is to improve the communication skills of students in boarding-based schools when learning economics through a cooperative learning model. This research uses quantitative methods with experiments.Â  Sampling used a cluster random sampling technique. The research sample is class X SMA Al-Irsyad Tegal which is based on boarding. Researchers conducted experimental research by giving each sample the same treatment. The results of the Paired t-test in this study show that the sig (2-tailed) value is 0.00 < 0.05. This means that applying the cooperative learning model can optimize communication skills. So, it can be concluded that the cooperative learning model implemented in high school based on boarding can be used as an alternative to improve communication skills